2020
DOI: 10.1016/j.psj.2019.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary probiotic (Pediococcus acidilactici) supplementation on productive performance, egg quality, and body composition in laying hens fed diets varying in energy density

Abstract: This study was conducted to determine the effect of probiotic Pediococcus acidilactici ( PA ) strain MA18/5M supplementation of diets with different dietary energy levels on productive performance, egg quality, and body composition in Hy-Line Brown hens during a 16-week period from 32 to 47 wk of age. The experimental treatments with a 2 × 2 factorial design received a 2 wheat–corn–soybean diet: a moderately low energy density diet with 2,650 kcal ME/kg ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 56 publications
(24 reference statements)
3
19
1
Order By: Relevance
“…Studies found that probiotic supplementation has effects on egg production [ 29 , 33 , 34 , 45 , 69 ]. The following variables were considered to evaluate egg production performance: ADFI, ADG, FCR, the number of the eggs laid, egg weight, specific gravity, serum and egg yolk cholesterol, and serum triglyceride.…”
Section: Laying Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Studies found that probiotic supplementation has effects on egg production [ 29 , 33 , 34 , 45 , 69 ]. The following variables were considered to evaluate egg production performance: ADFI, ADG, FCR, the number of the eggs laid, egg weight, specific gravity, serum and egg yolk cholesterol, and serum triglyceride.…”
Section: Laying Performancementioning
confidence: 99%
“…Improves laying performance and modulates the gut microbiota. [44][45][46] Propionibacterium acidipropionici…”
Section: Lactobacillus Sanfranciscensismentioning
confidence: 99%
“…When the treatment was continued for 24 h, it resulted in 52 ± 0.02% removal. In a similar way, Mikulski et al [33] have observed 12.33% cholesterol removal from egg yolk by Pediococcus acidilactici. With a step ahead, Lokapirnasari et al [34] aimed to study the combitorial effect of Bifidobacterium spp.…”
Section: Removal Of Cholesterol From Egg Yolk Under Gastrointestinal ...mentioning
confidence: 55%
“…To address global bans on the use of AGPs, the poultry industry has explored the use of probiotics, natural microbes that confer a beneficial effect on their host [ 12 , 13 ]. Single strain probiotic species including species of Streptococcus , Bacillus , Bifidobacterium , Enterococcus , Lactobacillus, Pediococcus and Saccharomyces , have been shown to have beneficial effects on broiler performance, laying hens, modulation of intestinal gut microbiota and pathogen inhibition [ 13 16 ]. However, probiotics have shown varying results between products and farms [ 17 ], limiting our understanding of their specific impact on the composition of the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%